Burden and clinical characteristics of recurrent Plasmodium vivax infections, and impact of primaquine for radical cure: a systematic scoping review in India - Kojom Foko, Loick Pradel; Singh, Vineeta (Frontiers in Malaria, 2024)
BackgroundIndia accounts for the bulk of Plasmodium vivax burden in South East Asia. Primaquine (PQ) is the only currently available drug for treating relapses in P. vivax malaria. MethodsHere, we provide an overview of the epidemiology and clinical characteristics of P. vivax recurrent infections in India and discuss current knowledge gaps and priority research areas for further investigations, with emphasis on relapses and their radical cure with PQ. Results and discussionA total of 27 studies involving ~27,000 P. vivax infected patients were finally included. Recurrent infections with P. vivax malaria are common, especially in young males. The burden of P. vivax relapse greatly varies across Indian regions, with a proportion range of 1.47 to 6% based on the included studies which all used low (very low) PQ dose. There is a need for more empirical data on the effectiveness and safety of weekly administration of PQ at 0.75 mg/Kg for eight weeks in G6PD–deficiency patients in India, especially in children. Further research priorities should also be focused on the epidemiology of confounding factor, such as CQ-resistance, mixed infections, or Pv genetic diversity are needed. The clinical impact of P. vivax relapses (e.g., severe malaria, mortality) is also of valuable interest in upcoming studies. More studies addressing the above-mentioned missing links should be implemented to inform malariologists, clinicians, populations, and policy makers on real situation of P. vivax relapses and the clinical impact of PQ in India. All taken together, these would have important implications for P. vivax malaria control and elimination in endemic areas.